SAS survival handbook : for any climate, in any situation - Wiseman, John, 1940-; Great Britain. Army. Special Air Service (New York, N.Y. : Collins, 2009)
A survival guide from the Special Air Service offers a complete course on how to be prepared for any type of emergency--from natural disasters to terrorist attacks to wilderness adventures--explaining how to adapt successfully to various climates, how to identify edible plants, and how to build a fire, with tips on first aid, campcraft, emergency preparation, and more. The SAS Survival Handbook is the Special Air Service's complete course in being prepared for any type of emergency. John Wiseman presents real strategies for surviving in any type of situation, from accidents and escape procedures, including chemical and nuclear to successfully adapting to various climates (polar, tropical, desert), to identifying edible plants and creating fire. The book is extremely practical and is illustrated throughout with easy-to-understand line art and diagrams.
Includes index.
Keywords: Survival